Transforming RNA-Based Gene Therapy with Innovative Nanocarriers for siRNA and miRNA Delivery - Chaudhary, Jitendra Singh; Chanchal, Dilip Kumar; Singh, Kuldeep; Gupta, Jeetendra Kumar; Jain, Divya; Dubey, Anubhav; Pandey, Mahima; Khan, Shahbaz (Current Gene Therapy, 2025)
The cells have been given precise instructions proprio to the regulation of gene expression by the main genesis of Ryan-based gene therapy, which has revived cancer treatment and other disorders. The difficulty of delivering small interfering RNA (siRNA) and microRNA (miRNA) to a target cell is an enormous task and is often faced by researchers due to characteristic instabilities of these carriers and their poor uptake by the cell membrane. The new developments from nanocarrier technologies offer opportunities for better effectiveness of RNA therapy for its delivery and the effectiveness of the treatment regimen. The objective of this article is to provide an overview of the existing as well as the newest developments in nanocarrier technology, particularly as related to microRNA and small interfering RNA (siRNA) delivery. Their modes of operation and their uses in gene therapies are also examined as principles of their design. We focus on several nanocarrier technologies, which have shown proof of concept in multiple disciplines such as stability, controlled release profiles, and delivery. Lipid-based nanoparticles, polymeric systems, and hybrid nanocarriers are some of the platforms that fall under this category; however, this list is not exhaustive. We also study the idea that certain nanocarriers could have multiple functionalities, which would make it possible to improve cancer treatment by simultaneously carrying chemotherapy and genes. We aim to shed light on the future of RNA-based gene therapy by providing a thorough overview of recent research in the field. This will help us understand how novel nanocarrier technologies can tackle the delivery issues.
Keywords: RNA-based gene therapy